Universal periodic review as a mechanism for monitoring human rights in Islamic states - Тейлор, Алла Валеріївна; Тейлор, А. В.; Taylor, Alla Valeriivna (Одеса : Фенікс, 2026)
The development of international mechanisms for monitoring human rights has led to the creation of new forms of supervision within the United Nations system. This mechanism combines elements of political dialogue with legal assessment and has gradually become an essential part of the international human rights framework. In the Islamic states, where the relationship between international norms and domestic legal traditions may raise specific questions, the UPR provides a useful framework for examining how international monitoring functions in practice. In relation to Islamic states, the UPR shows its potential and its limitations at the same time. It contributes to dialogue and may support gradual improvements, but its effectiveness largely depends on the willingness of states to implement the recommendations.
Taylor A. V. Universal periodic review as a mechanism for monitoring human rights in Islamic states. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 1. С. 265-267. URL: https://doi.org/10.32837/11300.33323
Keywords: права людини; моніторинг дотримання прав людини; міжнародне право; міжнародне право прав людини; Організація Об’єднаних Націй; Універсальний періодичний огляд (УПО); Рада Організації Об’єднаних Націй з прав людини; ісламські держави; human rights; human rights monitoring; international law; international human rights law; United Nations; Universal Periodic Review (UPR); United Nations Human Rights Council; Islamic states